2011
DOI: 10.21432/t2s598
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Benefits and Challenges of Using Laptop Computers in Higher Education Classrooms: A Formative Analysis

Abstract: Because of decreased prices, increased convenience, and wireless access, an increasing number of college and university students are using laptop computers in their classrooms. This recent trend has forced instructors to address the educational consequences of using these mobile devices. The purpose of the current study was to analyze and assess beneficial and challenging laptop behaviours in higher education classrooms. Both quantitative and qualitative data were collected from 177 undergraduate university st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 13 publications
9
77
0
11
Order By: Relevance
“…its distraction effect. Kay & Lauricella (2011a, 2011b, studying the use of laptops in imparting learning, have said that laptops provided benefits, including improved note-taking, improved organizational skills and improved collaboration among students. They also found that use of laptop posed challenges including distractions caused by students using instant messaging applications, playing games and watching movies instead of focusing on the class.…”
Section: Use Of Pc Tabs For Imparting Learning To Generation Zmentioning
confidence: 99%
“…its distraction effect. Kay & Lauricella (2011a, 2011b, studying the use of laptops in imparting learning, have said that laptops provided benefits, including improved note-taking, improved organizational skills and improved collaboration among students. They also found that use of laptop posed challenges including distractions caused by students using instant messaging applications, playing games and watching movies instead of focusing on the class.…”
Section: Use Of Pc Tabs For Imparting Learning To Generation Zmentioning
confidence: 99%
“…Moreover, disruption activities, such as instant messaging and web surfing also create problems when laptops were allowed to be used during lectures [8].…”
Section: Background Studymentioning
confidence: 99%
“…4 Some academicians believe that non-course-related use of e-devices is detrimental to learning and may interfere with the learning environment of others. 5,6 In support of this view, some students have reported that laptop use during class is distracting [7][8][9] and interferes with their ability to learn. 10 Despite some students' negative perceptions, laptop use has not been associated with poorer academic performance among non-laptop users.…”
Section: Introductionmentioning
confidence: 99%